Volume 2A: Turbomachinery 2018
DOI: 10.1115/gt2018-75132
|View full text |Cite
|
Sign up to set email alerts
|

Some Aspects of Transonic Compressor Tandem Design

Abstract: The development of modern axial compressors has already reached a high level. Therefore an enlargement of the design space by means of new or advanced aerodynamic methods is necessary in order to achieve further enhancements of performance and efficiency. The tandem arrangement of profiles in a transonic compressor blade row is such a method. It is necessary to address the design aspects a bit more in detail in order to efficiently apply this blading concept to turbomachinery. Therefore, in the current study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Although small enhancement was obtained during optimizing blade shapes and resetting some blade design parameters, a much larger aerodynamic improvement did not occur. 10 Hence, the advantages of tandem blade design that tandem blade could outperform the traditional single blade at highly loaded conditions have already been confirmed. However, no more significant large improvement could be expected by just adjusting basic parameters of blade arrangements.…”
Section: Introductionmentioning
confidence: 95%
“…Although small enhancement was obtained during optimizing blade shapes and resetting some blade design parameters, a much larger aerodynamic improvement did not occur. 10 Hence, the advantages of tandem blade design that tandem blade could outperform the traditional single blade at highly loaded conditions have already been confirmed. However, no more significant large improvement could be expected by just adjusting basic parameters of blade arrangements.…”
Section: Introductionmentioning
confidence: 95%
“…Under these conditions lower density causes higher kinematic viscosity resulting significant reduction of Reynolds number. At low Reynolds number conditions, the viscous losses dominate the flow which has a significant impact on the stability and operating range of the compressors [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, McGlumhy et al 11 evaluated the flow mechanics of a tandem rotor in the rear stages of a core compressor, which showed that the F blade acted in a similar manner to a conventional rotor, whereas the R blade tended to be more 3D and non-uniform. Hergt et al 12 studied some aspects of the design of tandem cascade under transonic operating condition. Basic design recommendations were extracted from open literature and optimization of a transonic compressor tandem cascade was performed, which resulted in a highly loaded, high efficient tandem compressor cascade and showed a good agreement with the recommended design aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Hergt et al. 12 studied some aspects of the design of tandem cascade under transonic operating condition. Basic design recommendations were extracted from open literature and optimization of a transonic compressor tandem cascade was performed, which resulted in a highly loaded, high efficient tandem compressor cascade and showed a good agreement with the recommended design aspects.…”
Section: Introductionmentioning
confidence: 99%